Graph ((x-9)^2)/9-((y-10)^2)/7=1

Math
(x-9)29-(y-10)27=1
Simplify each term in the equation in order to set the right side equal to 1. The standard form of an ellipse or hyperbola requires the right side of the equation be 1.
(x-9)29-(y-10)27=1
This is the form of a hyperbola. Use this form to determine the values used to find vertices and asymptotes of the hyperbola.
(x-h)2a2-(y-k)2b2=1
Match the values in this hyperbola to those of the standard form. The variable h represents the x-offset from the origin, k represents the y-offset from origin, a.
a=3
b=7
k=10
h=9
The center of a hyperbola follows the form of (h,k). Substitute in the values of h and k.
(9,10)
Find c, the distance from the center to a focus.
Tap for more steps…
Find the distance from the center to a focus of the hyperbola by using the following formula.
a2+b2
Substitute the values of a and b in the formula.
(3)2+(7)2
Simplify.
Tap for more steps…
Raise 3 to the power of 2.
9+(7)2
Rewrite 72 as 7.
Tap for more steps…
Use axn=axn to rewrite 7 as 712.
9+(712)2
Apply the power rule and multiply exponents, (am)n=amn.
9+712⋅2
Combine 12 and 2.
9+722
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
9+722
Divide 1 by 1.
9+71
9+71
Evaluate the exponent.
9+7
9+7
Simplify the expression.
Tap for more steps…
Add 9 and 7.
16
Rewrite 16 as 42.
42
Pull terms out from under the radical, assuming positive real numbers.
4
4
4
4
Find the vertices.
Tap for more steps…
The first vertex of a hyperbola can be found by adding a to h.
(h+a,k)
Substitute the known values of h, a, and k into the formula and simplify.
(12,10)
The second vertex of a hyperbola can be found by subtracting a from h.
(h-a,k)
Substitute the known values of h, a, and k into the formula and simplify.
(6,10)
The vertices of a hyperbola follow the form of (h±a,k). Hyperbolas have two vertices.
(12,10),(6,10)
(12,10),(6,10)
Find the foci.
Tap for more steps…
The first focus of a hyperbola can be found by adding c to h.
(h+c,k)
Substitute the known values of h, c, and k into the formula and simplify.
(13,10)
The second focus of a hyperbola can be found by subtracting c from h.
(h-c,k)
Substitute the known values of h, c, and k into the formula and simplify.
(5,10)
The foci of a hyperbola follow the form of (h±a2+b2,k). Hyperbolas have two foci.
(13,10),(5,10)
(13,10),(5,10)
Find the eccentricity.
Tap for more steps…
Find the eccentricity by using the following formula.
a2+b2a
Substitute the values of a and b into the formula.
(3)2+(7)23
Simplify the numerator.
Tap for more steps…
Raise 3 to the power of 2.
9+(7)23
Rewrite 72 as 7.
Tap for more steps…
Use axn=axn to rewrite 7 as 712.
9+(712)23
Apply the power rule and multiply exponents, (am)n=amn.
9+712⋅23
Combine 12 and 2.
9+7223
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
9+7223
Divide 1 by 1.
9+713
9+713
Evaluate the exponent.
9+73
9+73
Add 9 and 7.
163
Rewrite 16 as 42.
423
Pull terms out from under the radical, assuming positive real numbers.
43
43
43
Find the focal parameter.
Tap for more steps…
Find the value of the focal parameter of the hyperbola by using the following formula.
b2a2+b2
Substitute the values of b and a2+b2 in the formula.
724
Rewrite 72 as 7.
Tap for more steps…
Use axn=axn to rewrite 7 as 712.
(712)24
Apply the power rule and multiply exponents, (am)n=amn.
712⋅24
Combine 12 and 2.
7224
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
7224
Divide 1 by 1.
714
714
Evaluate the exponent.
74
74
74
The asymptotes follow the form y=±b(x-h)a+k because this hyperbola opens left and right.
y=±73⋅(x-(9))+10
Simplify to find the first asymptote.
Tap for more steps…
Remove parentheses.
y=73⋅(x-(9))+10
Simplify each term.
Tap for more steps…
Multiply -1 by 9.
y=73⋅(x-9)+10
Apply the distributive property.
y=73x+73⋅-9+10
Combine 73 and x.
y=7×3+73⋅-9+10
Cancel the common factor of 3.
Tap for more steps…
Factor 3 out of -9.
y=7×3+73⋅(3(-3))+10
Cancel the common factor.
y=7×3+73⋅(3⋅-3)+10
Rewrite the expression.
y=7×3+7⋅-3+10
y=7×3+7⋅-3+10
Move -3 to the left of 7.
y=7×3-37+10
y=7×3-37+10
y=7×3-37+10
Simplify to find the second asymptote.
Tap for more steps…
Remove parentheses.
y=-73⋅(x-(9))+10
Simplify each term.
Tap for more steps…
Multiply -1 by 9.
y=-73⋅(x-9)+10
Apply the distributive property.
y=-73x-73⋅-9+10
Combine x and 73.
y=-x73-73⋅-9+10
Cancel the common factor of 3.
Tap for more steps…
Move the leading negative in -73 into the numerator.
y=-x73+-73⋅-9+10
Factor 3 out of -9.
y=-x73+-73⋅(3(-3))+10
Cancel the common factor.
y=-x73+-73⋅(3⋅-3)+10
Rewrite the expression.
y=-x73-7⋅-3+10
y=-x73-7⋅-3+10
Multiply -3 by -1.
y=-x73+37+10
y=-x73+37+10
y=-x73+37+10
This hyperbola has two asymptotes.
y=7×3-37+10,y=-x73+37+10
These values represent the important values for graphing and analyzing a hyperbola.
Center: (9,10)
Vertices: (12,10),(6,10)
Foci: (13,10),(5,10)
Eccentricity: 43
Focal Parameter: 74
Asymptotes: y=7×3-37+10, y=-x73+37+10
Graph ((x-9)^2)/9-((y-10)^2)/7=1

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top